Lymphovascular Invasion: A Comprehensive Appraisal in Colon and Rectal Adenocarcinoma. Issue 6 (June 2015) - Hogan, John; Chang, Kah Hoong; Duff, Gerald; Samaha, Georges; Kelly, Niall; Burton, Michael; Burton, Emily; Coffey, John Calvin
Abstract : BACKGROUND: Colon and rectal adenocarcinomas differ at a multitude of levels. The association between outcome and predictor in 1 group may obscure the relationship between outcome and predictor in the other. OBJECTIVE: The current study aims to evaluate the prognostic properties of lymphovascular invasion in colon and rectal adenocarcinoma separately. MATERIALS AND METHODS (DESIGN, SETTING AND PATIENTS): A comparative retrospective analysis was undertaken to determine the prognostic properties of lymphovascular invasion in colon and rectal adenocarcinomas. Patients were classified as lymphovascular invasion positive and lymphovascular invasion negative in separate colon and rectal cancer cohorts. Within cohorts, a univariate analysis was undertaken to determine the association between lymphovascular invasion positivity and local/systemic recurrence and overall/disease-free survival. Findings were evaluated by using Kaplan-Meier estimates, log-rank analysis, and a Cox proportional hazards multivariate model. MAIN OUTCOME MEASURE: The primary outcomes measured were overall and disease-free survival. RESULTS: Five hundred twenty-seven patients were included in the analysis (379 with colon cancer and 148 with rectal cancer). On univariate analysis, lymphovascular invasion positivity was associated with adverse locoregional recurrence in colon ( p = 0.002) but not rectal adenocarcinoma ( p = 0.13). Conversely, lymphovascular invasion positivity was associated with adverse systemic recurrence in rectal ( p = 0.002) but not colon adenocarcinoma ( p = 0.35). On multivariate analysis, lymphovascular invasion positivity was an independent predictor of adverse disease-free survival in colon ( p = 0.02) and rectal adenocarcinoma ( p < 0.001). Regarding overall survival, lymphovascular invasion positivity was a poor prognostic indicator in rectal adenocarcinoma only ( p = 0.04). LIMITATIONS AND CONCLUSIONS: In this retrospective analysis, lymphovascular invasion positivity was associated with different patterns of disease recurrence in colon and rectal cancer. Lymphovascular invasion positivity was associated with adverse overall survival in rectal cancer only.